Ultra‐reduced phases in Apollo 16 regolith: Combined field emission electron probe microanalysis and atom probe tomography of submicron Fe‐Si grains in Apollo 16 sample 61500. (12th June 2017) - Gopon, Phillip; Spicuzza, Michael J.; Kelly, Thomas F.; Reinhard, David; Prosa, Ty J.; Fournelle, John
Abstract: The lunar regolith contains a variety of chemically reduced phases of interest to planetary scientists and the most common, metallic iron, is generally ascribed to space weathering processes (Lucey et al.2006 ). Reports of silicon metal and iron silicides, phases indicative of extremely reducing conditions, in lunar samples are rare (Anand et al.2004 ; Spicuzza et al.2011 ). Additional examples of Fe‐silicides have been identified in a survey of particles from Apollo 16 sample 61501, 22. Herein is demonstrated the utility of low keV electron probe microanalysis (EPMA), using the Fe Ll X‐ray line, to analyze these submicron phases, and the necessity of accounting for carbon contamination. We document four Fe‐Si and Si 0 minerals in lunar regolith return material. The new Fe‐Si samples have a composition close to (Fe, Ni)3 Si, whereas those associated with Si 0 are close to FeSi2 and Fe3 Si7 . Atom probe tomography of (Fe, Ni)3 Si shows trace levels of C (60 ppma and nanodomains enriched in C, Ni, P, Cr, and Sr). These reduced minerals require orders of magnitude lower oxygen fugacity and more reducing conditions than required to form Fe 0 . Documenting the similarities and differences in these samples is important to constrain their formation processes. These phases potentially formed at high temperatures resulting from a meteorite impact. Whether carbon played a role in achieving the lower oxygen fugacities—and there is evidence of nearby carbonaceous chondritic material—it remains to be proven that carbon was the necessary component for the unique existence of these Si 0 and iron silicide minerals.